Comparison of sexual function and quality of life after pelvic trauma with and without Angioembolization - Goussous, Naeem (Burns Trauma, 2015)
BACKGROUND: The aim is to study the safety of Angioembolization on long-term sexual function and quality of life. METHODS: IRB approval was gained to review the prospectively collected trauma database as well as prospective questionnaires of patients at least 1 year out from pelvic fractures that occurred between 1996 and 2009. Surveys included the SF36v2, Female Sexual Function Index and the International Index of Erectile Function. Values for each domain were compared between patients treated with AE and 2:1 case-matched control patients as well as between the national norms. Values are presented as percentages or means with 95 % CI. P < 0.05 was considered statistically significant. RESULTS: Thirty Seven cases and 74 matched controls were identified. 42 patients completed the survey. There were 13 cases (12 males), and 29 controls (22 males). There was a higher ISS (Injury Severity Score) (32 vs 27; p = 0.048) in the cases, but no difference in pelvic AIS (Abbreviated Injury Severity Score) (3 vs 3). Both groups scored similarly in the SF36 in all domains, but the entire cohort scored lower than the national norms in the physical functioning (41.9 (37.8–46.0) vs50), role physical (40.9 (36.2–45.7) vs50), body pain 43.8 (40.7–46.9) vs50), role emotional 46.3 (42.8–49.8) vs50), and physical composite score (42.1 (38.0–46.3) vs50). All domains of the sexual function in both questionnaires showed significant impairment in our cohort compared with norms. Male cases had similar scores to the controls. CONCLUSION: Pelvic fractures portend a worse long-term QOL and sexual function than the general population. AE, however, does not have an additive affect to these indices.